PENERAPAN MODEL INDEKS TUNGGAL UNTUK OPTIMALISASI PORTOFOLIO DAN PENGUKURAN VALUE AT RISK DENGAN VARIANCE COVARIANCE (Studi Kasus: Saham yang Stabil dalam LQ 45 Selama Periode Februari 2011 – Juli 2016) - Hanifa Eka Oktafiani; Di Asih I Maruddani; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
One of popular investments among investors is investing in a form of stock in go public companies. Investing stocks must not be separated from a wide variety of risks. One way to minimize risk is by taking a portfolio of several stocks. This research uses single index model to form portfolio of several stocks because it has simple computation than other method. This model based on the observation that price of securities have linier fluctuation with market indeks. Estimate of Value at Risk (VaR) can be calculated using variance covariance method which requires that return of a stock and return portfolio of several stocks have a normal distribution. This research aplicated to stable several stocks, in the meaning that always recorded in LQ 45 during February 2011 until July 2016. Based on 21 stable stocks in LQ 45, there are six stocks included in the optimal portfolio. That is stock of GGRM (Gudang Garam Ltd.), BBCA (Bank Central Asia Ltd.), JSMR (Jasa Marga Persero Ltd.), LPKR (Lippo Karawaci Ltd.), BBRI (Bank Rakyat Indonesia Persero Ltd.), and INDF (Indofood Sukses Makmur Ltd.), which estimated of VaR in a month after investing on optimal portfolio at 95% confidence level is Rp 7.846.572,00 from initial capital of Rp 100.000.000,00. Keywords: Portfolio, Stock, Single Index Model, Variance Covariance, LQ 45